Protective effects of avenanthramide-C against cisplatin-induced cardiotoxicity in rats by attenuating oxidative stress, inflammatory cytokines, and modulating p62–Keap1–Nrf2 pathway - Aldubayan, Maha Abdulrahman (Frontiers in Pharmacology, 2025)
IntroductionCisplatin (CIS) is widely recognized as a potent antineoplastic agent, especially effective for treating various solid tumors. Nevertheless, the pathological response it induces, alongside oxidative stress and inflammation from upstream reactions, causes varying degrees of damage to multiple organs in the human body. The primary adverse effects of CIS include nephrotoxicity, neurotoxicity, ototoxicity, and gastrointestinal toxicity. CIS-induced cardiotoxicity is rare, and its prevalence remains unknown. Avenanthramide-C (AVN-C), an antioxidant compound found solely in oats (Avena sativa L.), is recognized for its significant ability to neutralize free radicals; however, the mechanism by which it exerts other protective influences remains unclear. Research indicates that AVN-C significantly reduces the expression of gene transcripts responsible for encoding pro-inflammatory cytokines when exposed to H2O2 or tumor necrosis factor-α (TNF-α). This study investigated the potential protective role of the antioxidant and anti-inflammatory properties of AVN-C in mitigating CIS-induced cardiotoxicity in rat cardiac tissue.MethodsForty male Wistar rats were randomly assigned to 4 groups, each comprising an equal number of animals (10 animals per group), as follows: control (5%DMSO/Saline), CIS (CIS, 10 mg/kg), AVN-C (20 mg/kg), and CIS + AVN-C groups. Blood plasma was collected from the retro-orbital plexus for the evaluation of biochemical parameters, including lactate dehydrogenase (LDH), creatine kinase (CK-MB), and troponin I. Cardiac tissues were extracted to evaluate oxidative stress markers, including reactive oxygen species (ROS), malondialdehyde (MDA), and superoxide dismutase (SOD). Additionally, inflammatory markers such as TNF-α, interleukin (IL)-1β, IL-6, and nuclear factor kappa B (NF-κB) were assessed. The heart tissues were also examined for the protein and mRNA expressions for p62, Kelch-like ECH-associated protein 1 (Keap1), and nuclear factor erythroid 2-related factor 2 (Nrf2).ResultsThe CIS group exhibited significantly increased LDH, CK-MB, troponin I, MDA, ROS, TNF-α, IL-6, IL-1β, NF-κB, and Keap1 levels. However, AVN-C administration led to a significant reduction in these marker levels. Additionally, CIS + AVN-C treatment resulted in significantly increased p62, Nrf2, and SOD levels compared to the CIS group.ConclusionAVN-C may protect against CIS-induced cardiotoxicity by reducing oxidative stress and inflammation, possibly activating the p62-Keap1-Nrf2 pathway. Histopathologically, heart tissues treated with CIS + AVN-C were less damaged than tissues treated with the CIS group. These findings suggest AVN-C as a promising therapeutic agent against CIS-induced cardiotoxicity. Nonetheless, the absence of echocardiographic assessments remains a key limitation, and future studies incorporating these evaluations are warranted to strengthen translational relevance.